Building MPA Student Competence in the New 4Es through Teaching Cases. (3rd September 2022) - Mumford, Steven W.
Abstract: Public service education aims to prepare students to serve in the "public interest, " historically encompassing the "3Es" of efficiency, economy, and effectiveness. However, modern public servants must apply practical and moral wisdom to answer calls for administrators to address inequities and advance social justice. The field is thus implored to elevate social equity as a normative foundation and connect it to complementary values—including engagement, empathy, and ethics—comprising a set of "new 4Es" often overlooked in public administration curricula. But how might instructors teach the new 4Es in Master of Public Administration (MPA) coursework? Review of diverse literatures suggests the case teaching method, which assigns narrative case readings putting learners in the role of participant in a realistic dilemma and asks them to make a critical decision, holds promise for cultivating the new 4Es. Through an example of a foundational MPA management course, this article equips instructors with strategies for implementing the case teaching method and connecting cases to each of the new 4Es. The design, delivery, assessment strategies, and preliminary outcomes of the course are discussed. The article concludes with challenges and opportunities for public service educators to adopt the pedagogical approach within their own contexts.